Measuring the Apparent Magnitude of Planet Mars on August 1st and October 2nd, 2018 at the Falak Observatory at Muhammadiyah University of North Sumatera - Hidayat, Muhammad; Rakhmadi, Arwin Juli; Raisal, Abu Yazid (Universitas Ahmad Dahlan, 2020)
The Bright stars that were seen by the eyes are the received quantity of the energy flux sent from the celestial body. The energy flux is inversely proportional to the distant quadrant which means that the light of the stars that are visible to our eyes cannot be compared to the actual brightness or even weaker than the others and the visible star lights the apparent magnitude. The purpose of this study is to measure the apparent magnitude of Mars. This research methodology is quantitative, by taking number of images/videos of Mars and then the data is processed by using IRIS software. The results of the analysis is using IRIS software that shows the value of the apparent magnitude of Mars on August 1st, 2018 is (-1.56 Â± 0.33) and October 2nd 2018 is (-1.84 Â± 0.08). This was taken by selecting the best image result in clear night sky.